The acute effects of ankle mobilisations on lower extremity joint kinematics. Issue 4 (October 2017) - Howe, Louis P.
Abstract: Introduction: Previous investigations have identified compensatory movement strategies (CMS) within the lower extremity or lumbopelvic complex during closed chain exercises may be associated with a loss of ankle dorsiflexion range of motion (ROM). The aim of this study was to investigate the acute effects of ankle mobilisations on proximal joint kinematics during a movement task that demands a high amount of ankle dorsiflexion ROM. Methods: Eight healthy males (mean (SD) age 25 (4) years) demonstrating side-to-side asymmetry during the weight-bearing lunge test (WBLT) and CMS during the single-leg step-down exercise were accepted for this study. Participants completed five repetitions of a single-leg step-down, both before and after an ankle mobilisation intervention aimed at improving joint athrokinematics. A Vicon motion capture system recorded 3D joint and segment kinematics of the ankle, knee, hip and pelvis. A paired samples t -test was used to identify significant changes of lower extremity joint kinematics during the single-leg step-down, before and after mobilisation. Results: Following the mobilisation intervention, statistically significant gains in ankle dorsiflexion ROM were identified during the WBLT [mean difference 2.425 (0.9377) centimeters, t = −7.315, p < 0.01]. No evidence was found of altered joint kinematics during the single-leg step-down. Conclusion: These findings indicate that increases in ankle dorsiflexion ROM do not automatically integrate into functional movement tasks.